Type I Interferon-Induced TMEM106A Blocks Attachment of EV-A71 Virus by Interacting With the Membrane Protein SCARB2 - Guo, Xuemin; Zeng, Shinuan; Ji, Xiaoxin; Meng, Xiaobin; Lei, Nanfeng; Yang, Hai; Mu, Xin (Frontiers in Immunology, 2022)
Enterovirus A71 (EV-A71) and Coxsackievirus A16 (CV-A16) are the main causative agents of hand, foot and mouth disease (HFMD) worldwide. Studies showed that EV-A71 and CV-A16 antagonize the interferon (IFN) signaling pathway; however, how IFN controls this viral infection is largely unknown. Here, we identified an IFN-stimulated gene, Transmembrane Protein 106A (TMEM106A), encoding a protein that blocks EV-A71 and CV-A16 infection. Combined approaches measuring viral infection, gene expression and protein interactions uncovered that TMEM106A is required for optimal IFN-mediated viral inhibition and interferes with EV-A71 binding to host cells on the receptor scavenger receptor class B member 2 (SCARB2). Our findings reveal a new mechanism contributing to the IFN-mediated defense against EV-A71 and CV-A16 infection and provide a potential strategy for HFMD treatment by using the antiviral role of TMEM106A against enterovirus.